Sosialisasi Pemanfaatan Sampah Organik Menjadi Eco-enzyme Bagi Tim Penggerak PKK Rejoso, Nganjuk - Chrystia Aji Putra; Raden Balqis Ibrah Fakhira; Novia Nirmala Putri; Raihan Nur Rafi; Septian Nurul Istiqfaroh (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Rejoso, located in Nganjuk Regency, lacks adequate waste management facilities such as waste banks, composting, and landfills. Therefore, there is a pressing need to address waste management, particularly food waste. One effective method is converting organic waste, specifically leftover fruits and vegetables, into eco-enzyme. Members of the Tim Penggerak PKK can play a pivotal role in promoting organic waste management through eco-enzyme production. To facilitate this initiative, it is crucial to conduct a socialization, first and foremost, campaign on utilizing organic waste for eco-enzyme production among the Tim Penggerak PKK in Rejoso. This aims to foster sustainable and environmentally-friendly organic waste management practices. The approach involves three main activities: educating households on waste management, providing training on eco-enzyme production, and demonstrating the eco-enzyme production process.